MAJALAH ADIL DAN FRAMING ISU KRISTENISASI DI SURAKARTA TAHUN 1969-1970 - Ahmad Faidi; Adif Fahrizal Arifyadiputera (Aqlam: Journal of Islam and Plurality, 2022)
Abstract: This study attempts to trace the historical roots of Muslim-Christian relations in Solo. This research is a type of library research that uses a historical approach. The material objects of this research are articles, news, and opinions published in the magazine Adil 1969-1970. Issue Framing of Christianization in Solo by Adil Magazine is carried out by synchronizing 4 major themes, namely confusion in Christian theology, the Christianization movement is a movement that is contrary to the provisions of the Government in Indonesia, Christianization threatens the people of Indonesia. Militant Muslims, and lastly is the issue of Christian closeness with Communists.Keywords: Christianization, Adil Magazine, Issue FramingAbstrak: Penelitian ini berupaya melacak akar historis hubungan Islam-Kristen di Solo. Penelitian ini merupakan jenis penelitian Library research yang menggunakan pendekatan historis. Objek material dari penelitian ini adalah artikel, berita, dan opini yang diterbitkan majalan Adil 1969-1970. Framing isu Kristenisasi di Solo oleh Majalah Adil dilakukan dengan cara menerasikan 4 tema besar, yakni kerancuan dalam teologi Kristen, gerakan Kristenisasi merupakan gerakan yang bertentangan dengan ketetapan Pemerintah di Indonesia, Kristenisasi mengancam kaum Muslim Militan, dan terakhir adalah isu kedekatan Kristen dengan dengan Komunis.Kata Kunci: Kristenisasi, Majalah Adil, framing Isu